The Influence of Price, Product Quality, and Brand Image on Online Purchasing Decisions for Aquaponic Products at PT Tanikota - Delia Nada Suryana; Dini Rochdiani (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2023)
The COVID-19 pandemic has encouraged all activities to be carried out completely online, including purchasing fresh products to meet daily food needs. PT Tanikota is a company located in Bandung that sells aquaponic products online. Behind the existing business potential, consumers of fresh produce are still not sure to make purchases online because they cannot see or choose directly the products they want to buy, given their perishable characteristics. The purpose of this study was to analyze the effect of price, product quality, and brand image on online purchasing decisions for aquaponics at PT Tanikota. The design of this research is using mixed methods. The results showed that price and product quality had an effect on purchasing decisions for aquaponics products online at PT Tanikota, while brand image had no significant effect. Price, product quality, and brand image simultaneously have a significant effect on online product purchase decisions at PT Tanikota. The influence of price is 18.2%, product quality is 23.4% and brand image is 9.4%.